KONSTRUKSI KOPETENSI PROFESIONAL SARJANA EKONOMI SYARIAH PADA LEMBAGA KEUANGAN SYARIAH - Misnen Ardiansyah; Ibnu Qizam; Joko Setyono (State Institute of Islamic Studies (IAIN) Salatiga, 2013)
This study aims to analyze the perception of either students of higher education institutions of Islamic economics, or that of Islamic financial institutions, or that of institutions of sharia industry concerned with the competence of Islamic economics scholars. Data were obtained through the distribution of questionnaires in universities and branch offices of Islamic financial institutions in Yogyakarta selected by purposive sampling method. The analytical techniques used to address the hypothesis in this study was path analysis using the Partial Least Square (PLS) version 1.01. The results showed there is a positive influence of higher education institutions’ perceptions on students’ perceptions in the development of competence. However, both higher education institutions’ perceptions and students’ perceptions had no effect on the perception of the industry. This shows that there is still a gap between the competencies developed by higher education institutions and industrial needs.